Dose calculation and verification of the Vero gimbal tracking treatment delivery - Prasetio, Heru; Wölfelschneider, Jens; Ziegler, Marc; Serpa, M.; Witulla, Barbara; Bert, Christoph (Physics in Medicine and Biology, 2018)
The Vero linear accelerator delivers dynamic tumor tracking (DTT) treatment using a gimbal motion. However, the availability of treatment planning systems (TPS) to simulate DTT is limited. This study aims to implement and verify the gimbal tracking beam geometry in the dose calculation. Gimbal tracking was implemented by rotating the reference CT outside the TPS according to the ring, gantry, and gimbal tracking position obtained from the tracking log file. The dose was calculated using these rotated CTs. The geometric accuracy was verified by comparing calculated and measured film response using a ball bearing phantom. The dose was verified by comparing calculated 2D dose distributions and film measurements in a ball bearing and a homogeneous phantom using a gamma criterion of 2%/2 mm. The effect of implementing the gimbal tracking beam geometry in a 3D patient data dose calculation was evaluated using dose volume histograms (DVH). Geometrically, the gimbal tracking implementation accuracy was <0.94 mm. The isodose lines agreed with the film measurement. The largest dose difference of 9.4% was observed at maximum tilt positions with an isocenter and target separation of 17.51 mm. Dosimetrically, gamma passing rates were >98.4%. The introduction of the gimbal tracking beam geometry in the dose calculation shifted the DVH curves by 0.05%-1.26% for the phantom geometry and by 5.59% for the patient CT dataset. This study successfully demonstrates a method to incorporate the gimbal tracking beam geometry into dose calculations. By combining CT rotation and MU distribution according to the log file, the TPS was able to simulate the Vero tracking treatment dose delivery. The DVH analysis from the gimbal tracking dose calculation revealed changes in the dose distribution during gimbal DTT that are not visible with static dose calculations.
EVALuna2:33026

Quality assurance for dynamic tumor tracking - Witulla, Barbara; Ziegler, Marc; Brandt, Tobias; Prasetio, Heru; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2021)
The purpose of this work was to develop a treatment plan verification routine for a linear accelerator dedicated to SBRT treatments with gimbal based dynamic tumor tracking using three commercially available phantoms. The accelerator system has two special features: It operates with a rotation of the ring shaped gantry instead of a couch rotation and target motion can be compensated for via a gimbal system (dynamic tumor tracking, DTT). DTT plans were each measured with the three different phantoms. Afterwards the measured dose distribution was compared with the calculated dose distribution via global Gamma Index analysis (3 mm / 3%, threshold: 10%). The global gamma pass rates were on average (93.5 ± 7.2) % for ArcCHECK, (98.0 ± 2.6) % for OCTAVIUS® 4D and (98.4 ± 4.2) % for MatriXX Evolution. All three systems could be used for quality assurance with ring rotations and DTT, however, each with limitations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Intensity modulated radiation therapy; quality assurance; Stereotactic body radiation therapy; Tumor Tracking